Effect of single-layer density centrifugation on the quality of cryopreserved sperm of Cuniculus paca - Munera C., Daniela (2023)
Cuniculus paca is a terrestrial rodent that inhabits the neotropical forests of Central and South America. The aim of this study was to evaluate the effect of sperm separation on the quality of cryopreserved semen of C. paca. Sixty straws of frozen semen were thawed. One aliquot was subjected to sperm separation by single-layer density gradient centrifugation (SLC) and the other aliquot remained as a control group with semen not separated. Sperm motility and kinetics were evaluated using a computerized-assisted sperm analysis (CASA) system, functional membrane integrity by hypoosmotic test (HOST), and sperm morphology by eosin-nigrosin staining. The adjustment of linear models and comparison of means by Tukey was performed. The SLC separation produced a higher proportion of motile and linear spermatozoa, while the control showed higher values for curvilinear velocity (p˂0.05). Likewise, the SLC separation produced superior results for the vitality and functional integrity of the membrane (p˂0.05). It is concluded that the SLC separation of cryopreserved semen of C. paca allows obtaining samples with superior sperm quality characteristics, which could be used in repopulation programmes through assisted reproduction for this species.